The Verbal and Visual Signs of Memes Found on Pinterest - Abrahams, Ivana Victorya Maharani; Putri, I Gusti Ayu Vina Widiadnya; Santika, I Dewa Ayu Maharani (Journal of Language and Applied Linguistics, 2023)
This study concerns with the term of semiotics that is aimed at describing the verbal and visual signs as well as analyzing the functions and meaning of signs. The data of this study were taken from popular memes in 2020 on Pinterest or www.pinterest.com. The data were collected by observation method. The collected data were analyzed by descriptive qualitative method. Furthermore, the data were presented by formal and informal methods. There were three theories applied. The theory of semiotic was proposed by Saussure (1983), the theory of meaning was proposed by Barthes (1997). In addition, the theory of color was driven by Wierzbicka (1996). The result of this study showed that there were 6 verbal signs and 8 visual signs based on 3 data used in total. The visual signs are the most sign used on each meme. The purpose is to attract people on the internet when communicating with friends and shared for humorous purpose because it also conveys someone’s idea.